A new species of arboreal rat, genus Oecomys (Rodentia, Cricetidae) from Chaco - Pardiñas, Ulises Francisco J. (2016)
A new species of rodent is added to the highly diverse genus Oecomys (Cricetidae, Sigmodontinae, Oryzomyini)based on specimens collected in the Argentinian provinces of Chaco and Formosa. The new species ischaracterized by a derived carotid circulatory pattern, a feature shared with O. concolor, O. mamorae, and O. sydandersoni. A unique combination of morphological, morphometric, and molecular characters, however,provides unambiguous evidence of its validity as a separate entity. Individuals of the new species are larger thanother representatives of Oecomys, and their skulls have wide and cuneate interorbital regions with well-developedsupraorbital shelves, long incisive foramina, long palates, absent alisphenoid struts, and broad Eustachian tubes.This new Oecomys appears to be endemic to the Humid Chaco, an ecoregion listed as Vulnerable due to thehuman impact. Preliminary observations suggest that several specimens from Eastern Paraguay and the BrazilianPantanal could also be assigned to the new species described herein.